Parent-child book reading across early childhood and child vocabulary in the early school years: Findings from the Longitudinal Study of Australian Children - Zubrick, S; Farrant, Brad M (My University, 2013)
Vocabulary knowledge is a critical component of school readiness. The current study investigated the extent to which low levels of joint attention in infancy and parent-child book reading across early childhood increase the risk of children having poor vocabulary around the time of school entry. Relevant data from the Longitudinal Study of Australian Children were available for 2369 children (1211 boys) who had a median age of 9 months (M = 9.3 months, SD = 2.1 months) at wave 1 and a median age of 58 months (M = 58.0 months, SD = 2.5 months) at wave 3. As hypothesised, children who had low levels of joint attention at wave 1 were significantly more likely to have poor receptive vocabulary at wave 3. Furthermore, children who had low levels of parent-child book reading across early childhood were two and a half times more likely to have poor vocabulary at wave 3. These results converge with the findings of training studies and underline the importance of educating current and future parents about the pivotal roles of joint attention and parent-child book reading for children's language development and hence their readiness for school.
First Language
Keywords: Education and Training -- School readiness; Children -- Outcomes; Child Development -- Speech and Language; Childhood and child development; Learning, education and training; Children; Education and Training; Child Development; School readiness; Speech and Language; Outcomes; Childhood and child development; Learning, education and training